MicroRNAs and microbiota: Is there a cross talk? - Rizk, M.; Tuzmen, S. (Prous Science, Sau-Thomson Reuters, 2020)
MicroRNAs (miRNAs) are a form of single-stranded RNA molecules with a length that varies between 18 and 23 nucleotides and which are synthesized in the nucleus but function in the cytoplasm. miRNAs function endogenously and bind to complementary sequences in either the coding regions or the 3' untranslated regions (UTRs) of target messenger RNAs (mRNAs). This indicates that miRNAs operate in a post-transcriptional manner. miRNAs play essential roles in various biological events, and have thus been found extracellularly in different body fluids such as saliva, urine and plasma. miRNAs are distinguished in the gut mainly by examining content from intestines and feces. The gastrointestinal tract is infested with a variety of microorganisms that are initially inherited from the mother; however, those microorganisms develop as a result of changes in dietary intake and environmental factors. The gut microbiota are therefore shaped differently in different individuals due to several contributing factors such as genetics, diet and state of disease, and have a great impact on the host during phases of disease and homeostasis.
Keywords: miRNA; Microbiome; Gut microbiota; Gastrointestinal tract microorganisms; miRNA-mediated regulation; Microbial immunity regulation; Intestine barrier; Microbial dysbiosis